Residual beta-cell function in children with type 1 diabetes after a partial remission phase – a possible relation between C-peptide and betatrophin - Odyjewska, Emilia; Kupińska, Monika; Jamiołkowska-Sztabkowska, Milena; Bossowski, Artur; Głowińska-Olszewska, Barbara (Frontiers in Endocrinology, 2025)
IntroductionMaintaining endogenous insulin secretion in type 1 diabetes (T1D) long after its onset, and thus the need for early diagnosis and searching for factors preserving the secretory function of β-cells, has become an important goal of current research. The aim of the study was to evaluate C-peptide secretion in T1D children with at least 1 year disease duration and to investigate the potential role of body mass index (BMI) and betatrophin on residual β-cell function. We also assessed factors that may affect betatrophin levels.Methods121 children and adolescents suffering from T1D were divided into groups based on: clinical significance of C-peptide; BMI-SDS <1 and ≥1; and disease duration to compare C-peptide and betatrophin levels and determine the importance of these changes.ResultsOf the children recruited, 44 (36.36%) had clinically significant C-peptide (> 0.23 ng/ml), and compared with the group with clinically insignificant C-peptide they had later onset (P<.001), shorter duration of illness (P<.001), lower daily insulin requirement (P=.025), lower mean HbA1c over the past year (P=.002), higher betatrophin levels (P=.019), and BMI-SDS at diagnosis (P=.013). Betatrophin levels correlated positively with C-peptide (P=.043) while negatively with patient’s age (P<.001), BMI-SDS (P=.010), disease duration (P=.006), HbA1c level at sampling (P=.022), average HbA1c level over the past year (P=.006), and basal insulin (P=.001).ConclusionThe positive significant relationship between betatrophin and C-peptide concentrations may indicate betatrophin as a potential biomarker of long-lasting residual β-cell function. Negative correlation with BMI identifies the ongoing need to maintain an appropriate body mass.